IoT-based Weather Information Using WeMos - Gawande, Gopal S.; Kanwade, Archana B.; Deshmukh, Amar B.; Bhandari, Sheetal; Bendre, Varsha; Dakre, Anup G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The most modern internet innovation, known as the "Internet of Things" (IoT), continuously broadcasts real-time data on the state of the entire planet, including details on humidity, temperature, thunderstorms, earthquakes, floods, and other conditions that potentially jeopardise human life. Our study suggests a low cost weather informative and monitoring system that displays the output on an OLED display and retrieves the weather information for any place via a cloud database management system. This proposed method (system) is constructed on Arduino platform and employs a WeMos D1 board with an ESP8266-EX microcontroller to retrieves data from cloud. This paper’s major goal is to provide access to current data from any station while allowing users to view weather conditions at any place.